The Berenstain Bears and the red-handed thief - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1993)
Mr. Dweebish, the new teacher at the Bear Country School, tries to explain to the class bully how democracy works.
"2.3"--P. [4] of cover.
"007-011"--P. [4] of cover.
1 7 10 11 13 15 17 23 26 29 30 31 36
Keywords: Democracy -- Fiction; Bullies -- Fiction; Schools -- Fiction; Teachers -- Fiction; Bears -- Fiction